Judicial Treatment of Mut’ah and Retroactive Spousal Support: Jambi Religious Court Decision No. 1015/Pdt.G/2025/PA.Jmb - Marlina, Siti (Decisio: Journal of Judicial Law and Procedure, 2026)
This article analyzes judicial reasoning in determining nafkah iddah, mut’ah, and retroactive spousal support in divorce cases adjudicated by Indonesian Religious Courts. Using a normative juridical approach with a case-based analysis, the study examines the Jambi Religious Court Decision Number 1015/Pdt.G/2025/PA.Jmb to explore how judges operationalize Article 149 of the Compilation of Islamic Law within concrete adjudicative settings. The findings demonstrate that the provision functions as an open norm that requires judicial concretization through evidentiary assessment, evaluation of the husband’s economic capacity, and contextual interpretation of marital relations. Judicial reasoning in this case is characterized by the use of practical and relational reasoning, whereby normative mandates are integrated with socio-economic realities to balance women’s post-divorce economic rights and proportionality for the husband. The analysis further reveals that judicial discretion is exercised in a structured and accountable manner, supported by transparent argumentative links between legal norms, factual findings, and the operative part of the decision. This approach enables the court to avoid both mechanical application of legal norms and arbitrary decision-making. The study contributes to Islamic family law scholarship by demonstrating how judicial reasoning functions as a mediating mechanism between normative certainty and substantive justice. It also underscores the importance of coherent and reasoned judgments in strengthening the protection of women’s economic rights after divorce within Indonesia’s contemporary adjudicative framework, while offering insights for the development of more consistent judicial practices in religious courts.